DINAMIKA PARTAI POLITIK SEBAGAI GATEKEEPER DALAM MEMENUHI KUOTA PEREMPUAN DI JAWA BARAT - Rafih Sri Wulandari; Zaini Uzlah; Siti Mulyati (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2026)
This research aims to analyze the implementation of the affirmative action policy in fulfilling the women's quota within PDI Perjuangan in West Java Province. This issue is crucial due to the wide gap between the fulfillment of administrative quotas and the actual electoral results, which remain low in the field. Utilizing a qualitative approach with a case study method and Merilee S. Grindle's theoretical framework, this research evaluates the interaction between the content of policy and the context of implementation within the party. The research findings indicate that policy implementation has not been optimal due to decision-making that tends to be centralized, as well as the dominance of party elites acting as gatekeepers who limit the strategic space for female cadres. Affirmative policies are largely understood as an administrative obligation to comply with electoral regulations rather than as an instrument for substantive political transformation, often trapping them in the practice of tokenism. Other significant barriers include the strong influence of patriarchal culture, gender stereotypes, and the lack of operational support in the form of political education and sustainable funding at the local level. The study concludes that the success of this policy heavily relies on the commitment of local leaders and inclusive internal party reform so that women's representation is not merely symbolic, but capable of making a real impact on political decision-making.